An overview of technologies suitable for handling Indonesian agricultural soils contaminated with persistent organic pollutants - Dwindrata Basuki Aviantara; Mohamad Yani; Nastiti Siswi Indrasti; Gunawan Hadiko (Journal of Degraded and Mining Lands Management, 2022)
Since Indonesia have signed and ratified Stockholm Convention on Persistent Organic Pollutants (POPs) in 2009, the country must make efforts to manage POPs appropriately. A number of pollution evident of POPs has occurred in Indonesia, either air, soil or water. Agricultural soils are not excluded from POPs pollution as the result of halogenated pesticide uses or other unidentified sources. Contamination of POPs to humans have been detected, as well as indicated potential exposure of POPs to humans. Based-catalyzed decomposition is a method that can be used to decompose or decontaminate POPs. Limestone can be processed to produce calcium-based catalyst that can apply for POPs decomposition. Indonesia is a country rich in limestone natural resources to produce calcium. However, calcium is inferior to sodium or potassium in reactivity for the dehalogenation of POPs. Thus, more evaluation is needed in order for synthesizing proper and economical calcium-based catalyst to alleviate POPs pollution in Indonesia.